Nanobiocomposite: A New Approach to Drug Delivery System (Asian Journal of Pharmaceutics (AJP), 2016)
This article provides an overview on nanobiocomposite, their benefits, properties, methods of preparation, characterization, and application. The term nanobiocomposite combines benefits of nano size polymer, biodegradable polymer, and composite of polymers which provides the best platform for drug delivery. Nanobiocomposite contains two-phase system, of which, one has at least dimension lower than 100 nm. Nano size provides large surface area for interaction which results in beneficial properties. Benefits of nanobiocomposite include increase nanoparticle stability, increase water retention property, increase cellular uptake of drug, decrease inflammatory reaction, decrease hemolytic activity, and decrease degradation rate. The general method used for nanoparticle synthesis can be modified to prepare nanobiocomposite. Common methods of preparation are emulsion/solvent evaporation, emulsification solvent diffusion, emulsification solvent diffusion, solution intercalation, melt intercalation, double emulsion solvent evaporation, electrospinning, and ultrasonication. Sustained release, control release, antianemic, anticancer, antibacterial, and antifungal formulation can be prepared on nanobiocomposite platform. The objective of review is to enhance the use of nanobiocomposite as drug delivery system.